(untitled) (Al-Mansour Journal, 2023)
The operation of making decision of investment in developed projects demand using of available information to achieve the investment operation in adequacy and efficiency, just as to benefit from other sources in order to comply with the needs of developed economics in prefect way, because the issue of making decision links with the range of ability in obtaining the information in order to measure investment alternative and to compare between them, with in the scope of economic theory, in a regular style and high transparency Moreover, to act on the other side to prepare the basic requirements to salable the operation of developing the information systems to be capable of furnishing infrastructure to put the specialized information programs in the guided range to work towards manage and regulate the information as well as to use it high adequacy by managents revenue